Sudoku Puzzles for First-Year Organic Chemistry Students - Pérez Sánchez, Alice Lorena (2007)
We use sudoku puzzles to help the students (i) learn the correspondence between the names of the amino acids, their abbreviations, and codes and (ii) learn the correspondence between the names of the functional groups, their structures, and their abbreviations. This representation of information can be a fun way to learn details in chemistry.